2020
DOI: 10.1002/adom.202000557
|View full text |Cite
|
Sign up to set email alerts
|

Double Active Layers Constructed with Halide Perovskite and Quantum Dots for Broadband Photodetection

Abstract: Herein, solution‐processed, high‐performance broadband (300–1100 nm) photodetectors based on double active layers incorporating narrow‐bandgap CuInSe2 (CISe) quantum dots (QDs) and halide perovskite are devised. The CISe QDs/perovskite film as the photoactive layer boosts the photocurrent and suppresses dark current. Due to the joint light absorption effect of CISe QDs and halide perovskite, the photoelectric conversion capacity is improved. Furthermore, CISe QDs as an electron‐blocking layer can effectively b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…Narrow-bandgap materials, such as, inorganic QDs (e.g., PbS, CuInSe 2 , PbSe, etc. ), [47][48][49] polymers (e.g., poly(diketopyrrolopyrrole-terthiophene) (PDPP3T), poly{2,5-bis(2-hexyldecyl)-2,5-dihydropyrrolo [3,4- (DPP-DTT), etc. ), [50][51][52] small molecules (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Narrow-bandgap materials, such as, inorganic QDs (e.g., PbS, CuInSe 2 , PbSe, etc. ), [47][48][49] polymers (e.g., poly(diketopyrrolopyrrole-terthiophene) (PDPP3T), poly{2,5-bis(2-hexyldecyl)-2,5-dihydropyrrolo [3,4- (DPP-DTT), etc. ), [50][51][52] small molecules (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, photodetector based on perovskite with Si, [ 27 ] Ge, [ 28 ] ZnO [ 29,30 ] or PbSe, [ 31 ] CuInSe 2 , [ 32 ] have been successfully demonstrated, and the photo‐response can be covered from about visible region to near infrared region. [ 33 ] A brief summary of comparison of various photodetectors is shown in Table S1 (Supporting Information).…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23] However, it is difficult to produce perovskite with narrow bandgap and its absorption cutoff wavelength can hardly extend longer than 1000 nm. Therefore, a hybrid structure combining perovskite and traditional semiconductor materials is one of a promising alternative to realize a high performance broadband photodetector.Previously, photodetector based on perovskite with Si, [27] Ge, [28] ZnO [29,30] or PbSe, [31] CuInSe 2 , [32] have been successfully demonstrated, and the photo-response can be covered from about visible region to near infrared region. [33] A brief summary of comparison of various photodetectors is shown in Table S1 (Supporting Information).…”
mentioning
confidence: 99%
“…1−3 Because of their low preparation cost, high luminous efficiency, 4,5 adjustable band gap, 6,7 high absorption coefficient, 8,9 high carrier mobility, 10,11 and long diffusion length, 12,13 perovskites have become star materials for semiconductors and have been used in various optoelectronic devices such as solar cells, 14,15 light-emitting diodes, 16,17 lasers, 18,19 and photodetectors. 20,21 In recent years, it has been found that lead halide perovskites also have good properties in nonlinear optics (NLO), especially their third-order nonlinear absorption response, which makes their application in nonlinear optical materials and devices possible. 22,23 In this paper, the third-order and higher-order nonlinear optics of lead halide perovskites are reviewed.…”
mentioning
confidence: 99%
“…Their general formula can be represented as ABX 3 , in which A is a monovalent organic cation such as methylammonium (MA + ) or formamidinium (FA + ) or the inorganic metal ion Cs + , B is generally Pb 2+ , and X is a halide ion. In three-dimensional space, BX 6 octahedra form the three-dimensional skeleton via common vertexes, while A cations reside in the gaps of the octahedra. Because of their low preparation cost, high luminous efficiency, , adjustable band gap, , high absorption coefficient, , high carrier mobility, , and long diffusion length, , perovskites have become star materials for semiconductors and have been used in various optoelectronic devices such as solar cells, , light-emitting diodes, , lasers, , and photodetectors. , …”
mentioning
confidence: 99%